Macroeconomic determinants of Malaysia-Us Bilateral Trade Balance / Nor Fadhillah Abd Razak - Abd Razak, Nor Fadhillah (2018)
This paper was carried out to investigate the relationship between macroeconomic determinants and Malaysia-US bilateral trade balance from 1997 to 2017 containing a total number of 252 observations. Monthly time series data observations are used in multiple sets of tests such as Multiple Linear Regression, Descriptive Analysis, F-Test, Adjusted R-Squared, Normality Test, Correlation Analysis and Unit Root Test. According to past studies conducted by numerous researchers across years, they assessed that the trade balance between two countries exist and have significant relationship with fluctuation of floating exchange rate. TheE are also have been proved that other economic indicators such as gross domestic product (GDP), income, inflation, foreign direct investment and relative prices contributed to the change in country international trade. This research paper demonstrates the relationship between volatility of exchange rate and bilateral trade balance of Malaysia and United States. Other variables include domestic (Malaysia) income and foreign (United States) gross domestic products which both the economic growth of the respective nation. Appreciation and depreciation of domestic currency against foreign currency (MYR/USD) was believed would impact the export and import value of the local country. At the end of this study, we found that all independent variables except for exchange rate volatility portrayed positive and significant relationship towards Malaysia-US bilateral trade balance. The findings indicate that the bilateral trade of Malaysia and United States increases as income of Malaysia and United States increases. Meanwhile in contrast, when exchange rate volatility increases (currency devaluation), Malaysia-US bilateral trade balance worsens.